A Subtitling Analysis Of Imperative Sentence In Transformers: Revenge Of The Fallen Movie - Wulandari, Dyah Hafni (2012)
The objectives of this study are to describe the types of imperative sentence in subtitling, and to know the equivalence and non equivalence of imperative sentence with the target language in Transformers: Revenge of the Fallen movie. The writer employs descriptive qualitative method. By this method, the writer uses the subtitling of Transformers: Revenge of the Fallen movie as the source data, and the data are imperative sentence. The writer uses documentation technique in collecting the data. The collected data are analyzed by comparison method. The results of this research paper show that first, the writer finds that there are 2 types of imperative sentence, namely; (1) positive imperative sentence consisting 212 data or 87. 60 %, (2) negative imperative sentence consisting 30 data or 12. 39 %. The second, the writer finds that from 242 data, there are 226 data or 93. 38 % belong to equivalent subtitling and 16 data or 6. 61 % belong to non equivalent subtitling. So, the translation of subtitling Transformers: Revenge of the Fallen movie is good.